ANALISIS PERILAKU KONSUMSI MAHASISWA DALAM PERSPEKTIF EKONOMI ISLAM (STUDI KASUS PADA MAHASISWA UIN SUMATERA UTARA) - Aqil Muhammad Hasibuan; Putri Amirah Hajarani (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
This study aims to determine the consumption behavior of UIN North Sumatra students in the perspective of Islamic economics. The research method used is a qualitative approach. Data collection techniques used in this study were interviews and observation. The subjects used were active students from 2019 to 2022 studying at UIN North Sumatra. The results of this study indicate that UIN North Sumatra students have good consumption ethics, in consuming an item they prioritize interests over desires, pay attention to halal labeling, cleanliness, quality and benefits of the product to be purchased. North Sumatra UIN students are also aware of the importance of caring for one another, because behind the property we have there are other people's rights. Researchers hope that research can be useful, especially for students to be wiser in consumption